Apuntes sobre el “derecho a la ciudad”: revisiones teóricas y tensiones de un concepto ambiguo - Abraham, Eliana Isabel (2019)
In recent years there has been an accelerated growth in urbanization processes in different Latin American cities. The capital order is spatialized in urban scenarios that show differential ways of experiencing the city, where the relationship between space and society becomes an analytical key point to understand the current processes of social structuring. In this context, the “right to the city” bursts into the agenda of numerous sociocultural organizations and groups, in addition to becoming an argument for the design of public policies by current governments. This paper aims to reproblematize the concept of the “right to the city” by attempting to review its main backgrounds as an empirical registration of its instrumentation in local policies. For that purpose, we will refer to “urban laboratory experiences” developed by private agents within the framework of the Emerging and Sustainable Cities Program of the Inter-American Development Bank (IDB) in certain areas of experience. If the “right to the city” is assumed as a tool for the inclusion of governments to urban pariahs —according to Wacquant— for access to the city, what does it mean to think of this right when spatial inequalities intensify? Is the “right to the city” considered as a chimera for neighborhood groups and organizations or an argument for the practice of forms of violence sweetened by spatial capitalism?